Laws and Ordinances of the City of New York, Appendix containing certain acts of the Legislature which immeditely relate to the City and County of New York, at (1), An Act to prevent the Firing of Guns and other Fire-Arms within this State, on certain days therein mentioned (1793) - (:unkn) unknown (General Publisher, 1786)
if any person or persons, of what age, sex, or quality whatsoever, from and after the said first day of June next, shall fire and discharge any gun, pistol, rocket, cracker, squib or other fire-work, in any street, lane or ally, garden or other inclosure, or from any house, or in any other place where persons frequently walk, to the southward of Fresh-Water; that then every such person or persons so offending, and being thereof convicted before on or more justice or justices of the peace for the said city and county of New York, either by the confession of the party or parties so offending, or the oath of one or more witness or witnesses, (which oath the said justice or justices of the peace is and are hereby empowered and required to administer) shall, for every such offense, forfeit the sum of twenty shillings...
--
Keywords: DISCHARGE